SOLAR PARABOLIC TROUGH CONCENTRATOR SYSTEM DESIGN - VANIA ALINE (NIM : 13311012); RIZKY HARRY SUNGGUH (NIM : 13311067), GISELA
In 2010, many countries have realized the importance of using alternative energy resources other than fossil energy to sustain the demand for electricity. As the development of the population, fossil energy inventory was going down. Decresing of fossil energy inventory can be supported by the use of alternative energy sources, one of which solar energy. Indonesia, a country that lies on the equator, has more sunlight intensity with average of 4.8 kWh / m2 per day. The intensity of the sun that tends to be excessive can be used to convert solar energy into electrical energy or another energy forms by solar concentrator. This solar concentrator can be applied to a large open area and can be the main power source for residential as well as industrial purposes. In this research, reverse engineering design is useful as early studies for the development and application of solar concentrator in Indonesia. Results of geometric parameter can be used to calculate harvesting the energy produced by solar concentrator. Energy harvesting is determined through estimating the temperature obtained by the heat-absorbing pipe. The calculation result of solar concentrator found that the design of solar concentrator has focusing 10 cm, width 50 cm and depth of trough 15.6 cm is a type of solar concentrator with moderate temperatures. The potential for harvesting energy obtained from the test has a value that varies depending on environmental conditions, while the value thermal efficiency ranges in value of 28%.